Are Institutional Investors Really Skilled or Merely Opportunistic? - BERNILE, Gennaro (Institutional Knowledge at Singapore Management University, 2014)
Using a large dataset of institutional trades, we examine whether superior intraquarter trading performance of institutional investors reflects superior trading skill or opportunistic access to information. Our conjecture is that true investment skill would not depend upon geographical proximity between investors and firms, while opportunistic access to information is likely to be location-dependent. Thus, if institutions are truly skilled, they would earn high average return and exhibit performance persistence in both their local and nonlocal trades. Our evidence indicates that institutions on average are not skilled and their superior intraquarter performance is more likely to reflect opportunistic access to short-term local information. They have high average local performance but this performance is not persistent. Further, we observe increased local trading activity and profitability prior to earnings announcements, particularly before negative news. In contrast, the average net non-local intraquarter trading profits are not significantly different from zero. There is persistence in non-local performance, however, which suggests that some investors in the cross-section may be skilled. Specifically, investors with superior non-local performance exhibit superior future performance in both non-local and local trades. This evidence indicates that superior performance in non-local trades is a better indicator of innate trading skill.